Whole-genome sequencing of SARS-CoV-2 from residual viral RNA present on positive rapid antigen test kits for genomic surveillance - Anasir, Mohd Ishtiaq; Kamel, Khayri; Adypatti, Nor Malizza G; Jamaluddin, Mohammad Syafiq; Ahmad, Farah Amira; Norhisham, Siti Nurhidayah; Sukri, Muhammad Zulfazli Mohamad; Rosli, Nur Rafiqah; Saif, Siti Norazrina; Basarudin, Nurul Izzati; Azzam-Sayuti, Mohamad; Karim, Akmal Hayat Abdul; et al. (Western Pacific Surveillance and Response, 2025)
This report describes an approach to recover SARS-CoV-2 RNA from rapid antigen test kit (RTK-antigen) cassettes for whole-genome sequencing (WGS). RNA samples were recovered from 33 RTK-antigen cassettes for WGS, with 18 samples achieving more than 80% genome coverage. This work provides a proof-of-concept that positive RTK-antigen cassettes can be safely transported, stored and subjected to WGS, enabling swift identification of circulating variants.